Formation processes at the early Late Pleistocene archaic human site of Lingjing, China. (August 2018) - Li, Hao; Li, Zhan-yang; Lotter, Matt G.; Kuman, Kathleen
Abstract: Lingjing, located in northern China, is an open-air spring site dated to ∼90–125 ka through Optically Stimulated Luminescence (OSL) dating. Two late archaic human crania, which possess a mosaic of features indicative of both eastern Eurasian and Neanderthal ancestry, were excavated from the site, along with abundant animal fossils and stone artifacts. Despite Lingjing's obvious significance, detailed analyses of the processes that have influenced site formation and modification have not yet been performed. In this paper we provide an interpretation of the depositional context at Lingjing and we also provide an assessment of the level of site disturbance, both during and post-deposition. Sedimentary and archaeological indicators are employed in this study, and results show that there is differential modification of the stratigraphic horizons, primarily between lower layer 3 and the overlying upper layers 2 and 1. Although this disturbance is apparent, overall its extent is limited. The findings in this study therefore confirm that assemblage integrity at Lingjing is high, and that behavioural information is well preserved. Highlights: Differential modification of the stratigraphic horizons occurred at the site of Lingjing. The integrity or in situ nature of the lithic assemblage at Lingjing was not significantly altered. A variety of activities was carried out at Lingjing over a relatively long period of time. Our analysis at Lingjing provides a valuable reference and methodological framework for site formation studies in China.